Sex differences in MAGEL2 gene promoter methylation in high functioning autism - trends from a pilot study using nanopore Cas9 targeted long read sequencing - Jelte Wieting; Kirsten Jahn; Stefan Bleich; Maximilian Deest; Helge Frieling (BMC, 2024)
Abstract Background MAGEL2 is an autism susceptibility gene whose deficiency has been associated with autism-related behaviors in animal models and in syndromic human autism spectrum disorders (ASDs) such as Schaaf-Yang syndrome, but has not been studied in the broader autism spectrum. Given the capabilities of long-read sequencing technologies, this pilot study used a targeted nanopore sequencing approach to simultaneously examine MAGEL2 DNA sequence and methylation in adults with high-functioning autism (HFA) compared to neurotypical controls (NC). Methods Using DNA extracted from peripheral blood, Cas9-targeted nanopore DNA sequencing was used to analyze MAGEL2, including its entire regulatory construct (chr15:23639316-23651466), for sequence variation and 5-methyl-cytosine (5mC) modification in a cohort of adults with HFA compared to sex- and age-matched NC. Given the known sex differences in ASD and MAGEL2 KO animal models, results were further analyzed by sex. Results 20 adults with HFA (10 males, 10 females) and 20 NC were included. While there were no overall differences in MAGEL2 DNA sequence and 5mC modification between HFA and NC, we found a significant difference in MAGEL2 gene promoter methylation between males and females with HFA and NC of both sexes, with HFA males tending to show hypomethylation in a 300 bp long differentially methylated region (chr15:23647640-23647939) around the MAGEL2 transcription start site. Conclusions In this pilot study utilizing nanopore Cas9 targeted DNA sequencing, significant sex-specific differences in MAGEL2 gene promoter methylation were identified in male adults with HFA in comparison to control groups, suggesting the potential for sex-specific epigenetic differences. However, further replication in larger cohorts is required to validate these findings.